Rural Managerial Capacity and Administrative Performance and the Busung Rural Coastal Tourism Development Policy - Septiawan, Armauliza; Edy Akhyari; Rezal Hadi Basalamah; Pauzi (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
This research on the implementation of the rural Coastal Tourism Development policy aims to analyze the factors that affect the managerial ability of the Busung Village Government apparatus, Seri Kuala Lobam District, Bintan Regency to implement the coastal village development policy with a tourist character, also distinguishing the administrative performance overview of the Busung local rural Government, Seri Kuala Lobam District on Bintan Regency to realize the implementation of rural coastal tourism development policies. The research intends to empower data and information needed during research, namely data sourced directly from the research location through the  in-depth interviews practice that will be continuously empowered to develop a comprehent discussion of research in a qualitative approach in the descriptive form explanations of the phenomena that occur. The research findings confirm that the implementation of the rural government process is still not optimally colored by the involvement of community subjects as the main actors who participate in efforts to rural development at the research site.